2012
DOI: 10.1371/journal.pone.0037608
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Prediction of Multiple Drug-Target Interactions from Chemical, Genomic, and Pharmacological Data

Abstract: In silico prediction of drug-target interactions from heterogeneous biological data can advance our system-level search for drug molecules and therapeutic targets, which efforts have not yet reached full fruition. In this work, we report a systematic approach that efficiently integrates the chemical, genomic, and pharmacological information for drug targeting and discovery on a large scale, based on two powerful methods of Random Forest (RF) and Support Vector Machine (SVM). The performance of the derived mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
308
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 359 publications
(309 citation statements)
references
References 70 publications
1
308
0
Order By: Relevance
“…Structural superposition is another alternative approach to compare similar protein structures based on the root mean square deviation (RMSD) calculation [64]. Moreover, systematic integration of large datasets of target-ligand molecular interaction network data with multi-omics data enables to predict or design a potential lead molecule [60]. ii.…”
Section: Computational Methods For Lead Identificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Structural superposition is another alternative approach to compare similar protein structures based on the root mean square deviation (RMSD) calculation [64]. Moreover, systematic integration of large datasets of target-ligand molecular interaction network data with multi-omics data enables to predict or design a potential lead molecule [60]. ii.…”
Section: Computational Methods For Lead Identificationmentioning
confidence: 99%
“…ii. Maximum common substructure -It is a widely used method in CADD for finding similar 3D structures through structured-based or ligand-based virtual screening [60].Maximum common substructure search using SMILES (Simplified Molecular Input Line Entry System)pattern is commonly used to find structural similarity between large chemical datasets [65].The substructure search with compounds in the phenotype linked target-ligand interacting network datasets integrated with multi-omics data enables to predict or design a novel and potential lead molecule [66][67][68]. iii.…”
Section: Computational Methods For Lead Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…[26] developed three supervised inference methods to predict Drug-Target Interactions and used for drug repositioning, namely drug-based similarity inference (DBSI), target-based similarity inference (TBSI) and network-based inference (NBI). In addition, Yu et al [27] reported a systematic approach that efficiently integrates the chemical, genomic, and pharmacological information for multi drug targeting and discovery on a large scale, based on two powerful methods of Random Forest (RF) and Support Vector Machine (SVM). Finally, Singh-Blom et al [28] presented two methods for predicting gene-disease associations based on functional gene associations and gene-phenotype associations in model organisms, which is close to this work.…”
Section: Literature Surveymentioning
confidence: 99%